EVALUASI MEDIA BERBASIS WEBSITE UNTUK MEMBANTU MENGIDENTIFIKASI KARIR SISWA DI MAN 2 BANTUL, D.I. YOGYAKARTA - Ari Prasetyoaji; Riyan Wafaunnazmi; Salma Kartika Maharani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This research was conducted to evaluate media with career assistance for class XII students at MAN 2 Bantul, D.I. Yogyakarta by using a qualitative descriptive approach. Media evaluation helps this career using the Context, Input Process and Product evaluation model or what is often called the CIPP Evaluation Model. The basis for selecting this evaluation is because it covers more as a whole than other evaluation models. As the name implies, the aspects in this evaluation are Context, Process Input and Product. Context evaluation which is intended to examine the background of media production, Evaluation of input or input reviews regarding materials and supporting resources both facilities and infrastructure, Process Evaluation is evaluating users and also product evaluation, namely studying media results, helping careers developed. The focus of research on evaluating media assistance in career selection for class XII students at MAN 2 Bantul is based on a website. The hope of evaluating the development of this media is that the media will have better product quality and be more useful.